The Influence of the Hisbah Council on Dowry Policy in Islamic Law in the Southeast Asian Region - Mtd, Burhanuddin (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
This study aims to analyze the role and influence of the Hisbah Council on dowry policy in the context of Islamic law in the Southeast Asian region. The Hisbah Council as a religious institution has the authority to provide fatwas and guidance to Muslims. Using a descriptive qualitative research method, this article explores the dynamics of the Hisbah Council's decision-making, its policy implementation, and its impact on dowry practices in several countries in Southeast Asia such as Indonesia, Malaysia, and Brunei Darussalam. The results of the study show that the Hisbah Council contributes significantly in shaping public perceptions and practices related to dowry, both in its nominal and philosophical aspects. However, the role of the Hisbah Council is also faced with the challenges of modernity and cultural diversity in the region